Distribuição geográfica, análise fitoquímica, morfológica e uso de homeopatia Sulphur em caraguatá - Santos, Fernanda Lima dos (2017)
The caraguata (Eryngium elegans Cham. Et. Schleht.) Is a native plant of Rio Grande do Sul, with great potential to be exploited, aiming its preservation and valorization. This work aimed to identify the distribution of caraguatá exsicates in virtual herbaria, phytochemical composition and morphological characteristics by means of a survey and two experiments: 1) Survey of caraguatá exsicates in virtual herbaria (Eryngium elegans). It has been verified that exsicatas have been cataloged since 1829, in Brazil and other countries of Latin America; 2) Identification of the main chemical groups and some compounds of secondary metabolism, potentially medicinal, present in inflorescence, leaves and roots, was carried out by means of general identification tests and by high performance liquid chromatography (HPLC). General tests evidenced the presence of flavonoids and tannins in leaves and roots and saponins only in leaves by HPLC. It was verified presence of quercetin and caffeic acid in leaves, in the field treatment, where an experiment was carried out in a natural environment of the species, where the treatments were water (without homeopathy) and Sulphur 9 CH (with homeopathy) . In the treatment in pots, catechin stands out in the root, already the caffeic acid and ferulic acid in the leaves and inflorescences. The experiment in pots was implanted in the nursery of seedlings, where the treatments were Sulfur 9 CH, 10 CH, 11 CH, 12 CH and control. 3) For the morphological analysis the inflorescence, leaves and roots of the plants were collected. They were stained and photographed under an optical microscope. It was observed details of the external morphology of the caraguata, observing plant in an overview and later, each organ highlighted, after the anatomical structure of stem, leaf and root, analyzing the internal structure of the plant. In the course of this study, it is possible deepen studies on caraguatá, bringing in evidence this native species, for its valorization and medicinal potential.